Pengaruh Pertumbuhan Ekonomi Dan Tingkat Pengangguran Terbuka (TPT) Terhadap Kemiskinan Di Provinsi Jambi - Mawaddah, Alya; Abror, Ahmad Holil; Lestari, Apika; Nengsih, Titin Agustin (Universitas Negeri Padang, 2024)
This study analyzes the impact of economic growth and the open unemployment rate on poverty in Jambi Province using panel data from 11 regencies/cities during the 2020-2023 period. The panel data regression method with a random effect model approach was used in the analysis. The results show that economic growth has a negative and insignificant effect on poverty, while The results show that while the open unemployment rate has a positive and significant impact on poverty,economic growth has a negative and insignificant impact on poverty. At the same time, both economic growth and the open unemployment rate have a significant impact on poverty. influence on poverty in Jambi Province. These findings imply that poverty alleviation efforts need to consider improving economic growth and reducing the unemployment rate simultaneously to achieve optimal results.